Love, Existential Project, and Truth Seeking - Takwin, Bagus (Yayasan Jurnal Perempuan, 2018)
This paper explains what love is by referring to the philosophical thoughts of some philosophers and the results of empirical research that have been done on the phenomena of love. Here also discussed the tendency to extend love on one side, narrowing and even negating love on the other. This paper takes the position that love as an existential project. Philosophically, love is seen as a continuing search for truth. As the fruit of the will and the sincerity of human endeavor, love has real and concrete results. In its concrete form, love is the embodiment of a common promise into reality; a step-by-step process presents a concrete manifestation of the statements contained in the promise. This philosophical thought is corroborated by empirical studies of love that love differs from sexual passion or lust. Love can last long, eternal and stay intense through the couple’s efforts to care for each other, nurture and develop each other.